Advanced Cr(VI) sorption properties of activated carbon produced via pyrolysis of the "Posidonia oceanica" seagrass - Asimakopoulos, Georgios; Baikousi, Maria; Salmas, Constantinos; Bourlinos, Athanasios B; Zboril, Radek; Karakassides, Michael A (Journal of hazardous materials, 2021)
This research deals with the removal of Cr(VI), one of the most toxic heavy metal in biological systems, from wastewater by using activated carbon produced via pyrolysis and chemical activation of "Posidonia oceanica". That is the most important and well-studied seagrass species of the Mediterranean Sea. The as produced activated carbon exhibited high specific surface area up to 1563 m2/g and a cumulative pore volume of 0.74 cm3/g, allocated to 74% micro-pores and 26% to meso-macro- pores. The adsorption capacity of Cr(VI) into Posidonia oceanica activated carbon was studied via batch experiments considering the contact time, the initial concentration and the pH parameters. The results were interpreted using four different adsorption kinetic models. The activated carbon material seems to exhibit excellent sorption properties with rapid removal capability for Cr(VI). The estimated maximum uptake capacity at equilibrium stage was ~120 mg/g. Also, the initial adsorption rate ri was dependent on the initial Cr(VI) concentration in aqueous solution and it was from 77 mg/(g*h) to 264 mg/(g*h). The best fitted kinetic model seems to be the Diffusion-Chemisorption model with the rate constant KDC of the Cr(VI) ions transfer from liquid to solid particles extend from 52 to 78 mg/(g*h0.5).
Keywords: Pyrolysis; chemické látky znečišťující vodu; Alismatales; koncentrace vodíkových iontů; Mediterranean Sea; Water Pollutants, Chemical; kinetika; Hydrogen-Ion Concentration; Adsorption; pyrolýza; Kinetics; chrom; Charcoal; Středozemní moře; dřevěné a živočišné uhlí; Chromium; adsorpce